The role of stakeholders and their relationships in the sustainability of telecentres - Manh, Thai Do; Dang, Duong; Falch, Morten; Minh, Tuan Tran; Phi, Tuyen Vu (Emerald, 2023)
Purpose This paper aims to examine the role of stakeholders and their relationships in the sustainability of telecentres in Vietnam through the lens of stakeholder theory. Design/methodology/approach This study methodologically adopted a qualitative case study to identify stakeholders that have been involved in telecentres in Vietnam. It then categorizes those stakeholders’ salience through the lens of stakeholder identification and salience theory. Secondary data and interviews were used as data sources for the present paper. Findings The authors identify six main stakeholders that have been involved in telecentres, including the government, entrepreneurs, international donors, telecommunications providers, civil society organisations and individual community members/users. Among these stakeholders, the government, entrepreneurs and users belong to definitive stakeholders, which have the greatest impact on the sustainability of telecentres in comparison to other groups of stakeholders (e.g. dominant, dependent and dormant stakeholders). Moreover, the authors propose a model to identify the relationships of stakeholders towards the sustainability of telecentres. In particular, the authors indicate that each group of stakeholders has its own role in contributing to sustainable telecentres and they also influence others in either direct or indirect ways. Originality/value This study provides an additional approach for managers to make judgments in prioritizing the interests of some of their stakeholders while still maintaining a level of satisfaction among other stakeholders. For example, stakeholders that should be of the highest concern to the sustainability of telecentres are the government, entrepreneurs and users, while civil society organisations can be maintained in lower priority to other stakeholders. In addition, we propose the model of interactions and relationships of stakeholders, which can be seen as a starting point for a study on the roles of stakeholders in sustainability not only in telecentres, but also in other fields, such as digital transformation, cyber security and e-government.
Keywords: Role; Salience; Stakeholders; Sustainability; Telecentres; Vietnam; fi=Tietojärjestelmätiede|en=Information Systems|